Evaluation of the effect of favipiravir on patients with COVID-19 - Alireza Kamali; Hossein Sarmadian; Behnam Mahmoodiyeh; Shamim Valibeik; Farzane Farmani; Zahra Bashirgonbadi (Journal of Family Medicine and Primary Care)
Background: The novel coronavirus disease 2019 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) started in December 2019 in Wuhan, China. No specific drug has been accepted for COVID-19 treatment up to now. Favipiravir as an antiviral drug affects RNA viruses like influenza and Ebola. Accordingly, the aim of this study is the evaluation of favipiravir’s effect on COVID-19 outcomes. Method: This is a randomized controlled study including 97 patients with COVID-19 randomly allocated into favipiravir or control groups. The primary outcomes were improvement of clinical manifestations and atrial oxygen saturation (SpO2), and the secondary outcome was the length of hospitalization. Results: Clinical manifestations recovery of COVID-19 patients was better in the favipiravir group, and the mortality rates were less than in the control group (P = 0.0001 for both). The level of blood oxygen saturation (SpO2) was significantly higher in the favipiravir group (P = 0.0001). The mean lymphocyte count was lower in the control group (P = 0.004). In addition, levels of blood urine nitrogen (BUN) were higher in the favipiravir group (P = 0.033). The length of hospitalization was similar in both groups (P = 0.586). Conclusion: Favipiravir can be effective for clinical and laboratory improvement of COVID-19 patients, and it is a promising drug for decreasing of mortality rate in these patients.